2015
DOI: 10.4236/me.2015.67077
|View full text |Cite
|
Sign up to set email alerts
|

Cryptocurrencies: Are Disruptive Financial Innovations Here?

Abstract: Digital currencies, virtual currencies, in-game currencies, etc., have gathered a lot of attention, despite the difficulties of definition, from all corners of society for many years. Cryptocurrency has gained unprecedented attention since the birth of Bitcoin in 2009. Bitcoin is an online system of making and receiving payments in bitcoins. The system distinguishes itself by providing an opensource, cryptographically secure, confidentiality-preserving platform for transactions and/or making payments. The numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…These innovations included the technology behind the blockchain or ledgers and the decentralized ways of governance. Many authors have argued that the blockchain technology that works behind the cryptocurrencies is a potential breakthrough in financial innovation ( Glaser and Bezzenberger, 2015 ; Su et al., 2019 ; Vora, 2015 ). Olusegun Vincent& Olaniyi Evans (2019) also conducted an empirical study, showing that higher levels of financial inclusion and development were observed in China, India, Nigeria, and South Africa, for higher levels of cryptocurrency, internet usage, and mobile subscriptions .…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…These innovations included the technology behind the blockchain or ledgers and the decentralized ways of governance. Many authors have argued that the blockchain technology that works behind the cryptocurrencies is a potential breakthrough in financial innovation ( Glaser and Bezzenberger, 2015 ; Su et al., 2019 ; Vora, 2015 ). Olusegun Vincent& Olaniyi Evans (2019) also conducted an empirical study, showing that higher levels of financial inclusion and development were observed in China, India, Nigeria, and South Africa, for higher levels of cryptocurrency, internet usage, and mobile subscriptions .…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…In addition, there are more than 17 thousand cryptocurrency ATMs in 68 countries worldwide, and their number is increasing day by day (Coin ATM Radar, 2021). Businesses are inclined to accept cryptocurrency payments in addition to traditional payment methods to attract the attention of new generation consumers and achieve positive results on sales and marketing efforts (Vora, 2015;Andrei et al, 2019). The increasing adoption and spread rates of digital currencies have become the priority policies of some states and their international organizations.…”
Section: Cryptocurrencymentioning
confidence: 99%
“…(Ciaian and Rajcaniova, 2016). Also, businesses are inclined to accept cryptocurrency payments and traditional payment methods to attract the attention of new generation consumers and achieve positive results on sales and marketing efforts (Vora, 2015;Andrei et. all, 2019).…”
Section: Extended Abstractmentioning
confidence: 99%
“…2. Vora (2015) claims that cryptocurrencies and variants of virtual currencies are a welcome development, they will offer competition to the existing modalities of money and governmental regulation, they will provide alternative means to economic agents for their transactions, and their innovative existence should be encouraged so that their beneficial features outperform any deleterious ones. Bitcoins are here to stay suggest the above mentioned author, unless considered illegitimate by governments or banned by regulatory actions.…”
Section: Open Sourcementioning
confidence: 99%